Pengembangan Media Gambar untuk Meningkatan Kemampuan Menulis Teks Eksplanasi dengan Penerapan Model Project Based Learning - Fajar Fitri Zalukhu; Elisabeth Vierginia Asria Ningsih Zega; Frengki Faebua Dodo Daeli; Arozatulo Bawamenewi (Journal on Education, 2023)
This study intends to enhance the writing abilities of class VIII students at SMP Negeri 2 Gunungsitoli Utara through the construction of media pictures and the implementation of project-based learning learning models. This research is being developed through research (R&D). Researchers employed a questionnaire approach to gather data. Based on the study's findings, it can be concluded that project-based learning models and media pictures can help SMP Negeri 2 Gunungsitoli Utara class VIII students write explanatory texts more effectively.